Budaya Bahari Maluku dan Hubungannya dalam Perdagangan Rempah-Rempah Masa VOC, 1605-1799 - Pessy, Natalya Claire; Yulifar, Leli (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
This article highlights the Maluku islands as the center of the world spice trade, having a strong maritime culture and playing an important role in the dynamics of global trade during the VOC period (1605-1799). This research aims to explain the relationship between maritime culture and spice trade in Maluku and the legacy of maritime culture in Maluku. This research uses the historical method which consists of: heuristics, source criticism, interpretation, and historiography. The results showed that the maritime culture of the Moluccan people contributed greatly to building a global trade network while facing the pressure of colonialism. Thus, Maluku maritime culture has a close relationship with the spice trade during the VOC era, starting from the heritage of local boats, local wisdom related to the sea, and understanding of seasons, weather, and navigation owned by the Maluku people.